Determinants of the decision to adopt climate change adaptation strategies among smallholder upland farmers in Southeast Asia - Landicho, Leila D.; Van, Nam Le; Ximenes, Agusthino (Forestry Faculty, Universitas Hasanuddin, 2023)
This article argues that local adaptive capacity of the smallholder farmers determines their decision to adopt climate change adaptation strategies in the upland farming communities in the Philippines. This argument is based on the research conducted in the selected upland farming communities in the Philippines, Vietnam and Timor-Leste in 2017-2018 using the Local Adaptive Capacity (LAC) framework as the theoretical foundation. The study involved a survey of 637 upland farmers who were selected using simple random sampling; focus group discussion; key informant interviews; and, farm visits. Results revealed that the smallholder farmers across the three countries had low level of adaptive capacity. Binary logistics regression also indicates that leadership (p=.078) and innovations (p=.000) are the factors that influence farmers to adopt climate change adaptation strategies in the Philippines, while knowledge (p=0.000) and community assets (p=0.000) as the determinants among the smallholder farmers in Vietnam. In Timor-Leste, the decision to adopt climate change adaptation strategies are community assets (p=0.001), knowledge (p=0.000), and innovations (p=0.007). These results suggest an urgent need of enhancing the local adaptive capacity of smallholder farmers to be able to adapt to the impacts of climate change.